Allantoin and Amino Acid Composition in Xylem Exudates of Nodulated and Nitrate-dependent Cowpea Plants - Wan Othman, Wan Mohamad; Lie, T. A.; Mannetje, L. T. (Universiti Putra Malaysia Press, 1993)
The effects of Rhizobium inoculation and exogenous N concentrations (O, 0.5, 1.0, 2.0, 4.0 and 8.0 mM N as Ca(NO)21 on plant growth, nodulation, N2 fixation, amino acid composition and ureide abundance in xylem exudates of nodulated cowpea (Vigna unguiculata L. Walp cv. Kausband) were investigated in glasshouse-grown plants in sand culture. Without applied N, inoculation markedly increased N2fixation, top growth and allantoin concentration in exudates compared with the uninoculated control. Exogenous N, applied only to nodulated plants, had no beneficial effects on top, root or whole plant growth compared with inoculated control, but nodule mass and size and N2fixation decreased substantially with increasing N concentrations exceeding 1.0 mM. However, nodule number was unaffected lJy any N concentration. Allantoin concentration and relative ureide index {(ureide N/ total N in exudates) x 1001 declined drastically with N concentration, but the abundance ofN03-N in the exudates followed the reverse trend. In plants fully dependent on Rhizobium symbiosis, allantoin was the predominant (94 %) export product recovered in xylem exudates, with the remaining N solutes comprising of N03-N (4.5%) and amino-N (1.5%). Conversely, N03-N was the principal (87%) form of N exported in xylem of N03-dependent plants. Although 20 different amino acids were identified in the exudates, glutamine was the most abundant component (65%) in the nodule-dependent crop whereas asparagine was the predominant (43%) amino acid in the N03 dependent plants. Nodule mass and relative ureide index were highly and positively correlated (r = 0.959**).Allantoin concentration and Nz fixation had low correlation cotifJicient (r = 0.655 **). The significance of these data in biological nitrogen fixation studies is discussed.